Norway : Staff Report for the 2009 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper presents the staff report for Norway's 2009 Article IV Consultation on economic developments and policies. Unemployment remains low, and key short-term indicators point to a continued recovery. Norway's resilience has been underpinned by substantial macroeconomic stimulus, buoyant activity in the offshore hydrocarbon sector, high public sector employment, limited dependence on the hardest-hit segments of global manufacturing, and the relative stability of the domestic financial sector. Brisk oil sector activity, rising asset prices, and rapid credit growth have boosted the domestic demand.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet